Glocalization of Bull Racing: A Program for Preservation Kerapan Sapi as Madurese Local Wisdom - Nadi Suprapto; Suliyanah Suliyanah; Utama Alan Deta; Imam Sya'roni; Khoirun Nisa' (Kawalu: Journal of Local Culture, 2022)
The research-based on three backgrounds such as the competence and experience of researchers related to the context of local wisdom research; the potency of local wisdom in Madura; and the researchers are team teaching of the course physics local wisdom for Undergraduate Program of Physics education. Kerapan sapi is one of Madura's local cultures, which combines art, tradition, and competition. This type of research is a mixed-method with exploratory sequential design. The implementation of this research was carried out in Tengket Village, Bangkalan Regency. Data collection was collected based on observation, documentation studies, interviews, FGD, and questionnaires. The main object of this research is several Kerapan Sapi teams in Tengket Village, especially Trobos Sakti. Several factors for becoming the Kerapan Sapi champion were the division of team tasks, strategies to win, and support from the village government. Trobos Sakti divides his team's tasks into three parts: maintenance, competition, and owner sections; each part has its role. Trobos Sakti has several agendas and strategies for his race cows, such as feeding the cows with grass, exercising, bathing the cows, cleaning the cows' cages, and joining several competitions from regency level to national level. The contribution of Kerapan sapi to education is to open the understanding and application of Kerapan sapi culture to study material, especially physics material, in senior high school.